Workload-Aware Periodic Interconnect BIST - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Design &Test)
System-level interconnects provide the backbone for increasingly complex systems on a chip. Their vulnerability to electromigration and crosstalk can lead to serious reliability and safety issues during the system lifetime. This article presents an approach for periodic in-system testing which maintains a reliability profile to detect potential problems before they actually cause a failure. Relying on a common infrastructure for EM-aware system workload management and test, it minimizes the stress induced by the test itself and contributes to the self-healing of system-induced electromigration degradations.
Keywords: Electrical and Electronic Engineering; Hardware and Architecture; Software

Robust Pattern Generation for Small Delay Faults under Process Variations - Jafarzadeh, Hanieh; Klemme, Florian; Reimer, Jan Dennis; Najafi Haghi, Zahra Paria; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE International Test Conference (ITC'23), Anaheim, USA, October 2023)

Simplified numerical calculation of the isothermal, three-dimensional, Non-Newtonian flow characteristics of single-screw melt-extruder - Stüker, Daniel; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Introduction—The Digital Twin of Humans - Gräßler, Iris; Steffen, Eckhard; Maier, Günter W.; Roesmann, Daniel (The Digital Twin of Humans)

The Digital Twin of Humans

Calibration of a Contact Model for DEM Simulations of Grooved Feed Sections of Single Screw Extruders - Schöppner, Volker; Brüning, Florian (36th International Conference of the Polymer Processing Society (PPS-36))

Individual Assembly Guidance - Pöhler, Alexander; Gräßler, Iris (The Digital Twin of Humans)

The short-and long-term properties of welded high-temperature-resistant thermoplastics - Vogtschmidt, Sascha; Schöppner, Volker

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Analysis and modelling of the material degradation of polypropylene on the co-rotating twin-screw extruder - Altepeter, Matthias; Wanke, Sven; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Integration of Human Factors for Assembly Systems of the Future - Roesmann, Daniel; Gräßler, Iris (The Digital Twin of Humans)

Conceptions and Feasibility Study of Fiber Orientation in the Melt as Part of a Completely Circular Recycling Concept for Fiber-Reinforced Thermoplastics - Moritzer, Elmar; Tölle, Lisa; Greb, C.; Haag, M. (Journal of Composites Science)

Polypropylene Degradation on Co-Rotating Twin-Screw Extruders - Schöppner, Volker; Altepeter, Matthias; Austermeier, Laura; Wanke, Sven; Meinheit, Philipp (Polymers 2023)

Investigation of the Homogenization Performance of Various Faceted Mixers and Optimization with Regard to Mixing as well as Pressure Throughput Behavior - Schöppner, Volker; Frank, Maximilian

Design of a test bench for measuring the degradation behavior of plastics during processing - Schall, Christoph Wilhelm Theodor; Schöppner, Volker (PPS36)
Keywords: Computing Resources Provided by the Paderborn Center for Parallel Computing

Material Characterization of Polypropylene and Polystyrene Regarding Molecular Degradation Behavior - Schöppner, Volker; Schall, Christoph Wilhelm Theodor (Materials)

Characterization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian (Welding in the World)

POTENTIALS AND GOALS OF MODELS IN STRATEGIC PRODUCT PLANNING AND INNOVATION MANAGEMENT - Gräßler, Iris; Koch, Anna-Sophie; Tusek, Alena Marie (Proceedings of the Design Society)
Abstract New trends and technologies in product creation increase complexity, but at the same time create new potentials such as efficiency rise in task processing by Artificial Intelligence. Established models in the early phase of product creation such as the W-model or the Aachener Innovation Management model, do not fully exploit these new potentials in the field of strategic product planning and innovation management (SPPIM). For this reason, existing models are analysed in SPPIM in order to derive a requirements profile consisting of potentials and goals for a new model. A new model in SPPIM lays the foundation to support companies in enabling a more efficient task fulfilment by taking advantage of new technologies and trends. To guide the development of advanced SPPIM models, the derived potentials and goals are applied to the guideline VDI 2220:1980.

Interdependency study of design guidelines - Hesse, Philipp; Gräßler, Iris (Climate Protection, Resource Efficiency, and Sustainable Engineering: Transdisciplinary Approaches to Design and Manufacturing technology.)

Sustainable product life cycle - Hesse, Philipp; Gräßler, Iris (Climate Protection, Resource Efficiency, and Sustainable Engineering: Transdisciplinary Approaches to Design and Manufacturing technology.)